Changes in Oral and Salivary Contents in Patients with Chronic Kidney Disease - Bakhtawar Farooq; Abida Jaffar; Zahid Habib Qureshi; Nabeela Yasmeen; Rafay Ur Rehman (Life and Science)
Objective: To analyze oral manifestations and changes in salivary contents in patients with chronic kidney disease (CKD). Study Design: A comparative study. Place and Duration of Study: This study was conducted at the Nephrology Department of Ibne-Sina Hospital Multan, Pakistan from January 2021 to the Nephrology January 2023. Methods: Patients diagnosed with chronic kidney disease were included in the study after giving informed consent. The study was conducted on 100 subjects: 50 were chronic kidney disease (patients (study group), and 50 were period on tally and systematically healthy participants (control group). Saliva samples of all participants were collected and sent to a laboratory for detailed analysis. Results: The chronic kidney disease (CKD) patients had significantly reduced salivary flow compared to the healthy controls (P<0.001). The major oral manifestation in the study group was the the study group was the paleness of mucosa followed by calculus formation and bleeding of gums. The salivary sodium level in healthy controls was 13.4 ± 8.6, while in dialysis patients, it was 34.1 ± 19.3; this difference was statistically significant (P<0.001). Potassium level in control group was 19.2 ± 3.8 and in the study group was 22.5 ± 3.1 (P<0.001). The calcium level in the control group was 6.6 ± 2.1, and in the study group was 4.32 ± 4.55 (P<0.001). The Phosphorus level in control group was 5.5 ± 3.8 and study in study group was 27 ± 4.45 (P<0.001). Conclusion: Salivary calcium, phosphorus, urea, sodium, and potassium levels in chronic kidney disease are significantly higher than those in normal individuals. These increased levels are correlated with the severity of renal disease. Decreased salivary flow rate and calculus deposition reflect increased salivary urea and renal disorder.